The Influence of Elderly With Chronic Diseases On Cognitive Function Disorders Using MoCA INA at the Getasan District Elderly Posyandu - Arninta Rahma Khoirunnisa; Rufaida Amaturrohman (The International Journal of Medical Science and Health Research, 2025)
Populations at risk of dementia, such as the elderly, people with chronic diseases (hypertension, diabetes mellitus, hypercholesterolemia, and stroke), and a family history of senility, require early detection of dementia. People with chronic diseases need cognitive function screening to determine the future risk of dementia. The purpose of this study was to determine the relationship between the elderly with chronic diseases and cognitive function disorders using the MoCA-INA screening. This type of research used a cross-sectional study design using multivariate analysis with binary logistic regression to determine the correlation between variables. The results of the data analysis showed that there was a significant difference with respect to hypertension, diabetes mellitus, or both, age, gender, and education level (Elementary School and Junior High School). It was concluded that elderly individuals who have chronic diseases can affect cognitive function, resulting in a status of mild cognitive impairment.